Dietary exposure of the Belgian population to mineral oil. Issue 2 (1st February 2020) - Van Heyst, Annelies; Goscinny, Séverine; Bel, Sarah; Vandevijvere, Stefanie; Mertens, Birgit; Elskens, Marc; Van Hoeck, Els
ABSTRACT: Recently, presence of mineral oil in numerous foods has been detected. The analysis of mineral oil in food is convoluted since it comprises MOSH (saturated hydrocarbons) and variable amounts of mainly alkylated MOAH (aromatic hydrocarbons). Both fractions have a different toxicological profile and therefore they need to be assessed separately. For Belgium, occurrence data are available comprising concentrations of 217 food samples. These data were used, in combination with the 2014/15 Belgian Food Consumption Survey data, in a lower bound scenario to evaluate the dietary exposure of the Belgian population. Exposure to mineral oil was much lower compared to the results previously reported by EFSA and RIVM. The main contributors in Belgium were similar to previous studies (i.e. cereal products and oils), but an important additional contribution of non-alcoholic drinks was identified due to the presence of mineral oil in coffee. However, the concentration of mineral oil was determined from the dry product by applying a dilution factor with transfer rate of 100%, and not in the prepared coffee. This study gives an account of the dietary exposure of the Belgian population to mineral oil for the first time and reports the associated uncertainties. GRAPHICAL ABSTRACT: